Urban Gardens as a Space to Engender Biophilia: Evidence and Ways Forward - Lin, Brenda B.; Egerer, Monika H.; Ossola, Alessandro (Frontiers in Built Environment, 2018)
Cities are losing green space, driving an extinction of nature experiences for urban communities. Incremental green space loss can trigger a ratcheting-down effect where individuals’ expectations of nature continually decrease through time. This loss of everyday nature experiences may produce a citizenry with reduced knowledge and appreciation of biodiversity and the environment. In this review, Wwe examine how urban gardens, as urban spaces that bring people into close contact with nature in an otherwise built environment, can combat this ratcheting-down effect by encouraging interactions and knowledge of nature. Although the primary purpose of urban gardening may be food production, they also represent areas of social and recreational value as well as environmental education and knowledge sharingWe review three ways urban gardens may engender greater: 1) the provision of natural elements to expose urban dwellers to the diversity of plants, animals, soils that they would otherwise not encounter in their daily life; 2) fostering a greater understanding of natural processes that affect food production (e.g. climate processes, pest control, pollination) and thus the natural world; and 3) the provision of a safe space in which humans can corporeally interact with nature elements to develop greater fascination with nature. Urban gardeners, by interacting with soil, plants, and animals in these spaces, come into direct contact with a range of environmental elements. The practice of growing food and plants means that gardeners learn about environmental processes, such as pollination or changes in precipitation, and how they affect plant growth. Thus, urban gardens can engender biophilia for their participants by increasing exposure, positive interactions, and knowledge of nature, potentially changing people’s attitudes to nature. We present examples fromof a variety of urban gardens to show how these spaces can be designed using biophilic thinking to enhance people’s everyday nature experiences and their drive to interact with the natural world.